RESPIRATORY SYSTEM INFECTIONS AND THEIR CORRELATION WITH ABO BLOOD GROUP IN DIFFERENT AGE GROUPS IN KIRKUK CITY (World Bulletin of Public Health, 2022)
Respiratory tract infection; RTI is considered one of the most common infections that occurs in winter and infects all ages in both gender in human. In this regard, many studies investigated different parameters that could correlate with this type of infection and inflammation. However, a little is known about its relation with blood group. Therefore, this study hypothesised that the differences in the ABO blood groups could have a correlation with RTI. Samples were taken from patients who diagnosed for RTI in the period from January to March 2022 from both gender aged 20-70 years. About 146 sputum samples were collected; 82 males and 64 females. The results showed that from all samples, about 43.1% (63) males and 33.5% (49) females were positive for RTI, whilst other samples showed non-bacterial infections. Microbiological diagnosis of sputum showed different bacteria that cause RTI. Streptococcus pneumonia showed highest percentages of 25.9% in 29 patients, followed by 17.8% of M. pneumonia in 20 patients, about 16% K .pneumonia in 18 patients. Legionella showed 12.5% in 14 patients and to less percentages in both H. influenza (11.6% in 13 patients) and S.aureus 8.9% in 10 cases respectively. The least infection was seen in S. pyogenes (7.1% in 8 cases). These results correlated with blood group were RTI patient’s carrying blood group O showed 54% RTI while AB group was 6%.
Keywords: Respiratory Tract Infection; ABO blood group; Streptococcus pneumonia